A comparison of token and tandem schedules of reinforcement on response patterns for adolescents with autism. (13th December 2019) - Glodowski, Kathryn R.; Bourret, Jason; Ivy, Jonathan W.; Seaver, Jonathan P.; Jackson, Joshua; Stine, Julie M.; Nuzzolilli, Andrew E.
Abstract : Token schedules of reinforcement are ubiquitous in clinical settings, yet little research has thoroughly evaluated the effects of token schedules on responding in clinical settings. Basic research has shown token schedules of reinforcement produce lower response rates and larger pre‐ratio pauses compared to tandem schedules. The purpose of the current study was to determine whether the same effects are produced with adolescents with autism or related disorders. We examined response patterns under otherwise identical FR token and FR tandem schedules. Tokens suppressed responding for one participant only under high schedule values and for a second participant under common clinical schedule values; no difference in responding occurred between token and tandem schedules for two participants. These results support the systematic evaluation of token schedules of reinforcement in clinical settings. Additional applied research is needed on token schedules to further our understanding of the underlying mechanisms that contribute to the overall effectiveness of token economies.